Neocolonialism and science diplomacy: personal reflections from the Middle East on mental health policy and practice - Dabbagh, Nadia Taysir (Frontiers in Public Health, 2024)
Neocolonialism has led to an imbalance in the production of knowledge and a clunky imposition of frameworks and models of practice that do not meet the needs of local communities. In contrast they can serve the central function of colonialism by draining valuable resources. Inequity of science diplomacy has diluted local voices and given precedence to colonialist knowledge and models of practice. It is argued that clinical, training and research excellence applies to those activities that meet and fulfil the clinical, training and research needs of the community in which they are embedded. Through personal reflection on contrasting Middle Eastern settings (Palestine and the UAE), the call is for the source of knowledge production and the driver for innovation to be daily clinical experiences listening to families in the community. This will result in policy and practices that are meaningful and impactful as illustrated by way of three examples: (1) a narrative approach to exploring suicide (2) an “all-hands-on-deck” clinical pathway for Autism assessments which transformed the lives of children and families with little additional resource, but with a fundamental shift in approach from “top down” to “bottom up” one as part of an organization-wide “Patient First” approach and (3) a rights-based, collective approach to developing mental health strategy. These examples are linked in terms of taking a shared “listening approach” but are applied to different levels moving from personal individual narratives to community clinical service to national strategy.